2005
DOI: 10.1242/dev.01683
|View full text |Cite
|
Sign up to set email alerts
|

Reelin signaling is necessary for a specific step in the migration of hindbrain efferent neurons

Abstract: The cytoarchitecture of the hindbrain results from precise and co-ordinated sequences of neuronal migrations. Here, we show that reelin, an extracellular matrix protein involved in neuronal migration during CNS development, is necessary for an early, specific step in the migration of several hindbrain nuclei. We identified two cell populations not previously known to be affected in reeler mutants that show a common migratory defect: the olivocochlear efferent neurons and the facial visceral motor nucleus. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 47 publications
0
55
1
Order By: Relevance
“…Nevertheless, reelin could act in partnership with various receptors. Among them, apolipoprotein E receptor 2/very-low-density lipoprotein receptor (Rossel et al, 2005) and cadherin-related neuronal receptors family of protocadherins (Jossin, 2004) were recently proposed. To date, no reelin expression has been detected in ION (Schiffmann et al, 1997), and the expression domain of protocadherins in the developing hindbrain has been poorly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, reelin could act in partnership with various receptors. Among them, apolipoprotein E receptor 2/very-low-density lipoprotein receptor (Rossel et al, 2005) and cadherin-related neuronal receptors family of protocadherins (Jossin, 2004) were recently proposed. To date, no reelin expression has been detected in ION (Schiffmann et al, 1997), and the expression domain of protocadherins in the developing hindbrain has been poorly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a normal complement of GnRH-secreting neurons in the hypothalamus of mutants lacking both lipoprotein receptors and in scrambler mice lacking Dab1 is consistent with the in vitro findings. Although we are at present unable to identify a mechanism that mediates the action of reelin in this neurendocrine system, it is worth noting that effects of reelin, independent of the conventional reelin signalling pathway, have recently been described (Rossel et al, 2005) in the developing mouse hindbrain. These authors identified a ventral reelin-dependent migration that is independent of the receptors, ApoER2 and Vldlr.…”
Section: Mutants Of the Reelin Signalling Pathwaymentioning
confidence: 93%
“…In the mammalian cortex, neurons are generated in ventricular germinal zones and migrate radially towards the pial surface to form architectural layered structures. In mouse embryos, Reelin signaling regulates the positioning of neurons during layer formation of the cerebrum (reviewed by Tissir and Goffinet, 2003), and is essential for radial migration of the nVII motor neurons (Ohshima et al, 2002;Rossel et al, 2005). These data suggest that similar mechanisms regulate the proper positioning of both the hindbrain motor neurons and the cortical layer neurons.…”
Section: Novel Roles Of the Frizzled And Celsr Family Genes In Brain mentioning
confidence: 97%
“…In mouse hindbrain, guidance cues emanate from r5 and r6 to attract the nVII motor neurons (Studer, 2001). These may include Reelin (Ohshima et al, 2002;Rossel et al, 2005) and Sdf-1 (Sapede et al, 2005) signaling. In the present study, we have clearly shown that the neuroepithelial cells function in preventing integration of the nVII motor neurons into the neuroepithelial layer of the hindbrain, and that this radial exclusion is essential for normal migration of the nVII motor neurons.…”
Section: Neuroepithelial Cells Prevent Integration Of Nvii Motor Neurmentioning
confidence: 99%